Monarchia kastylijsko-aragońska czy Hiszpania? Wokół sporu o model państwa Królów Katolickich (1474–1516) - Kubiaczyk, Filip (Studia Europaea Gnesnensia, 2010)
It is quite commonly believed that the modern history of Spain begins with the reign of the Catholic Kings—Isabel I of Castile and Ferdinand II of Aragon, whose marriage was the cornerstone of the Castilian-Aragon union. Still, many historians are of the opinion that the notion of Spain in times of the Catholic Kings was purely geographic in nature, therefore Isabel and Ferdinand cannot be called rulers of Spain. My article undertakes polemics with such standpoint, and proves that already in the Spanish Middle Ages one spoke of Spain, moreover, not merely in the geographical sense, but with a historical and religious-cultural community in mind. I also draw on the evidence inherent the fact that Isabel and Ferdinand were called “kings of Spain” by their contemporaries, across Iberian Peninsula and beyond it. When analysing the motives behind concluding union by the two rulers, I demonstrate that for Isabel, Spain of the time was identical with what was Castilian, whereas Ferdinand entertained a genuine vision of Spanish unity, which rose above regional and particular perspectives. In equal measure, this dichotomy determined the shape of the monarchy of the Catholic Kings as well as its internal working, which was far from harmonious. In the conclusion, I point out that that the concept of Spain was most completely manifested in the foreign policy of the monarchy which was essentially steered by Ferdinand.